The Antarctic ozone hole during 2015 and 2016 - Tully, MB; Andrew Klekociuk; Krummel, PB; Gies, HP; Simon Alexander; Fraser, PJ; Henderson, SI; Schofield, R; Shanklin, JD; Stone, KA (2020)
We review the 2015 and 2016 Antarctic ozone holes, making use of a variety of ground-based and space-based measurements of ozone and ultra-violet radiation, supplemented by meteorological reanalyses. The ozone hole of 2015 was one of the most severe on record with respect to maximum area and integrated deficit and was notably long-lasting, with many values above previous extremes in October, November and December. In contrast, all assessed metrics for the 2016 ozone hole were at or below their median values for the 37 ozone holes since 1979 for which adequate satellite observations exist. The 2015 ozone hole was influenced both by very cold conditions and enhanced ozone depletion caused by stratospheric aerosol resulting from the April 2015 volcanic eruption of Calbuco (Chile).